A Ku-band 3.4 W/mm power AlGaN/GaN HEMT on a sapphire substrate - 王东方 陈晓娟 刘新宇 (Journal of semiconductors, 2010)
This paper describes the first domestic Ku-band power AlGaN/GaN HEMT fabricated on a sapphire substrate. The device with a gate width of 0.5 mm and a gate length of 0.35μm has exhibited an extrinsic current gain cutoff frequency of 20 GHz and an extrinsic maximum frequency of oscillation of 75 GHz.Under VDS=30 V,CW operating conditions at 14 GHz,the device exhibits a linear gain of 10.4 dB and a 3-dB-gain-compressed output power of 1.4 W with a power added efficiency of 41%.Under pulse operating conditions,the linear gain is 12.8 dB and the 3-dB-compressed output power is 1.7 W.The power density reaches 3.4 W/mm.